Pengaruh Dimetil Sulfoksida Terhadap Penetrasi Ketokonazol Melalui Membran Sel Difusi Franz - Auzal Halim; Maizel Fitri; Maria Dona Octavia (Jurnal Farmasi Higea, 2013)
Evaluation about the effect of dimethyl sulfoxide in ketoconazole gel formulation and its penetration using Franz diffusion cell membrane has been done. This gel formulation was using base are dimethyl sulfoxide and tragacant. The vertical type cell of Franz diffusion cell, was used for the penetration test and its quantity determination was done by using spectrophotometry method. The ketoconazole penetration quantity and its capacity of penetrating from dimethyl sulfoxide and tragacanth base are F1: 8.34µg/mL and 21.275%, F2: 10.36µg/mL and 13.705%  F3: 6.56 µg/mL and 16.318% then F4: 10.36µg/mL and 26.030%.